The Influence of Bio Natural Dye on the Optical Properties of Liquid Polyvinyl Alcohol - Salih Abbas Habeeb; Nardin Adnan Birtio; Hanaa Jawad Kadhim (Advanced Aspects of Engineering Research Vol. 15, 2021)
The use of bio liquid electrolytes in solar cells improves the efficiency of the cell, reduces the resulting electrostatic charge on the surface and reduces the potential leakage of solid electrolyte. The research aims to prepare liquid electrolyte of polyvinyl alcohol in addition to yellow dye extracted from flowers. The yellow dye of the flowers growing in Carthage, Tunisia, was extracted using acetone and diluted with ionized water to prepare different concentrations of dye. The dye molecules works as a collector of light and is produced excitation of electrons .Polyvinyl alcohol was dissolved in 100 ml of various solvents (water, diluted dye and concentrated dye) separately to obtain a constant concentration of all solutions 0.01 g / ml. optical. The optical properties, including absorbance, transmittance, and energy gap using ultraviolet spectrum were studied. Results proved that the optical properties including absorbance, absorption coefficient increased with increasing dye concentration, transmittance decreased with increasing of the pigment concentration. The energy gap decreases by increasing the concentration of the dye and has the lowest value at the concentrated dye about 1.7 eV. However, when adding the concentrated dye to the polyvinyl alcohol, the energy gap decreases from 4 eV to 1.8 eV.